1989
DOI: 10.1073/pnas.86.7.2493
|View full text |Cite
|
Sign up to set email alerts
|

Striatal phosphoproteins in Parkinson disease and progressive supranuclear palsy.

Abstract: This study was undertaken to evaluate the levels of cAMP-regulated phosphoproteins in the striatum of patients with neurodegenerative diseases of the dopaminergic system. Postmortem samples of caudate nucleus and putamen from 24 control subjects, 23 patients with Parkinson disease, and 13 patients with progressive supranuclear palsy were studied with immunoblotting techniques. The levels of tyrosine hydroxylase were reduced in patients with Parkinson disease (levels were 24% and 10% of controls in caudate nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 19 publications
(25 reference statements)
4
29
1
Order By: Relevance
“…Multiple preclinical studies using various experimental models have suggested that DARPP-32 may be critically involved in the response to several drugs of abuse (Bibb et al, 1999;Girault and Greengard, 2004); however, no clinical studies that have supported these observations have been published to date. Although no significant alterations in DARPP-32 levels were found in Parkinson's disease patients (Girault et al, 1989b), substantial evidence exists that indicates a role of the DARPP-32-related signaling network in the development of L-DOPA-induced dyskinesia in these patients (Santini et al, 2007).…”
Section: B Abnormalities In G Protein-related Dopamine Signaling In mentioning
confidence: 99%
“…Multiple preclinical studies using various experimental models have suggested that DARPP-32 may be critically involved in the response to several drugs of abuse (Bibb et al, 1999;Girault and Greengard, 2004); however, no clinical studies that have supported these observations have been published to date. Although no significant alterations in DARPP-32 levels were found in Parkinson's disease patients (Girault et al, 1989b), substantial evidence exists that indicates a role of the DARPP-32-related signaling network in the development of L-DOPA-induced dyskinesia in these patients (Santini et al, 2007).…”
Section: B Abnormalities In G Protein-related Dopamine Signaling In mentioning
confidence: 99%
“…Levels of D 1 R (Shinotoh et al, 1993;Turjanski et al, 1997;Hurley et al, 2001) and major mediators of D 1 R signaling, including PKA and DARPP-32 (Girault et al, 1989;Nishino et al, 1993), are unchanged in PD and its animal models. In MSNs, D 1 Rs and adenosine A 2A receptors (A 2A Rs) are coupled to adenylyl-cyclase through a heterotrimeric G-protein comprising G␣ olf , G␤2, and G␥7 subunits (Drinnan et al, 1991;Hervé et al, 1993;Kull et al, 2000;Zhuang et al, 2000;Corvol et al, 2001;Schwindinger et al, 2003Schwindinger et al, , 2010.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms of D 1 R hypersensitivity are unclear, because in contrast to D 2 receptor (D 2 R) (Creese et al, 1977;Lee et al, 1978), D 1 R number appears unchanged (Shinotoh et al, 1993;Turjanski et al, 1997;Hurley et al, 2001). Although functional D 1 hypersensitivity could be mediated by an increase in the activity of downstream effectors, several key proteins mediating D 1 R signaling, including protein kinase A and dopamine-and cAMP-regulated phosphoprotein , are unaltered in PD (Girault et al, 1989;Nishino et al, 1993). However, the possibility of alterations at the level of G-proteins that couple D 1 R to adenylyl cyclase has not yet been explored.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of protein levels in human postmortem samples could be affected by several confounding variables, including postmortem delay (PMD), age, and gender (Girault et al, 1989). To evaluate the effects of such variables, we first examined the levels of G␣olf, G␣s, G␣q, and G␥7 proteins as well as those of TH, DARPP-32, and ␤-actin in putamen samples of 23 controls (13 men and 10 women) from 56 to 90 years of age, with a PMD ranging from 1.3 to 24 hr.…”
Section: Brain Samples and Patient Characteristicsmentioning
confidence: 99%